Polubić ten wątły obrys — dwie próbki z Roberta Creeleya - Bartczak, Kacper (Poznańskie Studia Polonistyczne. Seria Literacka, 2009)
The present sketch discusses two poems written by R. Creeley, a poet initially associated with the Black Mountain College group, who later worked out his own idiosyncratic style, often referred to as minimalistic. Focusing on the two poems of the poet, one early poem and the other written towards the end of the poet’s life, the author of the article attempts to show how Creeley’s poetical technique, being remarkably disciplined and innerly organized variety of free verse, became his answer to the problem of contingency. Contingency, i.e. a lack of metaphysical protection, forms now the basic element of the poet in the democratic world. To facilitate this new modern understanding of the relationships between poetry and democracy, the author juxtaposes Creeley with Whitman in an attempt to outline post-religious spirituality close at hand for the poet who has no illusions as to human condition and who, at the same time, retains his creative power and drive that Creeley inherits from Whitman and Emerson.